The Sedimentary Carbon-Sulfur-Iron Interplay – A Lesson From East Anglian Salt Marsh Sediments - Antler, Gilad; Mills, Jennifer V.; Hutchings, Alec M.; Redeker, Kelly R.; Turchyn, Alexandra V. (Frontiers in Earth Science, 2019)
We explore the dynamics of the subsurface sulfur, iron and carbon cycles in salt marsh sediments from East Anglia, United Kingdom. We report measurements of pore fluid and sediment geochemistry, coupled with results from laboratory sediment incubation experiments, and develop a conceptual model to describe the influence of bioturbation on subsurface redox cycling. In the studied sediments the subsurface environment falls into two broadly defined geochemical patterns – iron-rich sediments or sulfide-rich sediments. Within each sediment type nearly identical pore fluid and solid phase geochemistries (in terms of concentrations of iron, sulfate, sulfide, dissolved inorganic carbon, and the sulfur and oxygen isotope compositions of sulfate) are observed in sediments that are hundreds of kilometres apart. Strictly iron-rich and strictly sulfide-rich sediments, despite their substantive geochemical differences, are observed within spatial distances of less than five meters. We suggest that this bistable system results from a series of feedback reactions that determine ultimately whether sediments will be sulfide-rich or iron-rich. We suggest that an oxidative cycle in the iron-rich sediment, driven by bioirrigation, allows rapid oxidation of organic matter, and that this irrigation impacts the sediment below the immediate physical depth of bioturbation. This oxidative cycle yields iron-rich sediments with low total organic carbon, dominated by microbial iron reduction and no methane production. In the absence of bioirrigation, sediments in the salt marsh become sulfide-rich with high methane concentrations. Our results suggest that the impact of bioirrigation not only drives recycling of sedimentary material but plays a key role in sedimentary interactions among iron, sulfur and carbon.